2015
DOI: 10.1038/ng.3370
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of mycosis fungoides and Sézary syndrome identifies recurrent alterations in TNFR2

Abstract: Mycosis fungoides and Sézary syndrome comprise the majority of cutaneous T cell lymphomas (CTCLs), disorders notable for their clinical heterogeneity that can present in skin or peripheral blood. Effective treatment options for CTCL are limited, and the genetic basis of these T cell lymphomas remains incompletely characterized1. Here we report recurrent point mutations and genomic gains of TNFRSF1B, encoding the tumor necrosis factor receptor TNFR2, in 18% of patients with mycosis fungoides and Sézary syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
263
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(288 citation statements)
references
References 30 publications
18
263
0
7
Order By: Relevance
“…Two other groups have recently reported the identification of the CTLA4-CD28 fusion gene in Sézary syndrome, an aggressive rare variant of cutaneous T-cell lymphoma. 25,26 That this mutation is not limited to Sézary syndrome but is found in a broad range of TCL types with an overall frequency of 30% and typically in combination with other mutations should be of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Two other groups have recently reported the identification of the CTLA4-CD28 fusion gene in Sézary syndrome, an aggressive rare variant of cutaneous T-cell lymphoma. 25,26 That this mutation is not limited to Sézary syndrome but is found in a broad range of TCL types with an overall frequency of 30% and typically in combination with other mutations should be of significance.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, amplifications and activating mutations in the CARD11 and the TNFRSF1B gene encoding the tumor necrosis factor receptor 2 (TNFR2) were identified in up to 30% of patients with high-stage CTCL. [14][15][16] These mutations cause constitutive signaling through the noncanonical NF-kB pathway in CTCL cells, further enhancing their cell death resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] These studies have now confirmed, expanded, and functionally validated many of the genetic aberrations detected by aCGH in MF/SS, a broad and diverse spectrum that include genes associated with T-cell receptor (TCR) signaling, activation of NF-kB, JAK/STAT signaling, chromatin remodeling, and DNA damage response. However, despite a significant degree of overlap, there was great variability in the identity and frequency of alterations at putative driver genes across studies.…”
mentioning
confidence: 73%